The impact of culling on production and profit - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1985)
Profit or loss in the dairy enterprise is dependent upon yearly production per cow and degree of capitalization. Higher producing cows convert feed into milk more efficiently. Cows of similar body size have similar maintenance requirements, regardless of level of yearly production. The successful dairy enterprise must establish yearly production goals needed to satisfy cash flow requirements and then implement management procedures to obtain maximal yearly milk per cow on the number of cows required to meet the herd's goal.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Culling; Production